2006
DOI: 10.1186/1476-4598-5-60
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The correlation between epigenetic aberrations and disease underscores the importance of epigenetic mechanisms. Here, we review recent findings regarding chromatin modifications and their relevance to cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(47 citation statements)
references
References 152 publications
0
47
0
Order By: Relevance
“…It has been previously reported that the normally fluctuating expression of ICBP90 in cycling cells is perturbed in most cancer cell lines (5,18,21,42). Since there is increasing evidence suggesting a role for epigenetic mechanisms in carcinogenesis (12,62), it would be interesting to determine if the role of ICBP90 in cancer is dependent upon its methyl K9 H3 binding activity. Our results outline several similarities of ICBP90 and Np95 and HP1, particularly the alpha and beta isoforms, such as recognition of methyl K9 H3, heterochromatic localization, and involvement in the establishment and/or maintenance of a higher-order chromatin organization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that the normally fluctuating expression of ICBP90 in cycling cells is perturbed in most cancer cell lines (5,18,21,42). Since there is increasing evidence suggesting a role for epigenetic mechanisms in carcinogenesis (12,62), it would be interesting to determine if the role of ICBP90 in cancer is dependent upon its methyl K9 H3 binding activity. Our results outline several similarities of ICBP90 and Np95 and HP1, particularly the alpha and beta isoforms, such as recognition of methyl K9 H3, heterochromatic localization, and involvement in the establishment and/or maintenance of a higher-order chromatin organization.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a multistep process derived from combinational crosstalk between genetic alterations and epigenetic influences through various environmental factors [5,6,7]. In the nutritional field, epigenetics is exceptionally important, because nutrients and bioactive food components can modify epigenetic phenomena and alter the expression of genes at the transcriptional level [2,8,9].…”
Section: Epigenetic Overview Of Crcmentioning
confidence: 99%
“…Increasing evidence suggests that bioactive dietary components impact epigenetic processes often involved in the reactivation of tumor suppressor genes, the activation of cell survival proteins and the induction of cellular apoptosis in many types of cancer [11]. In addition to the transcriptional silencing of tumor suppressor genes and protein expression, noncoding miRNAs also regulate the expression of a myriad of cellular proteins by affecting mRNA stability and translation by epigenetic processes in cancer progression [5,6]. Interestingly, miRNAs can control the expression of various epigenetic modifying enzymes, such as DNA methyltransferases, histone methyltransferases, and HDACs, involved in carcinogenic processes [12,13].…”
Section: Epigenetic Overview Of Crcmentioning
confidence: 99%
“…DNA that is normally methylated becomes unmethylated, while DNA that is supposed to be methylation free obtains the modification (Herman et al 1996;Baylin 2005;Feinberg et al 2006). This apparent redistribution of normal methylation patterning is regionally complex and is thought to be among the earliest molecular alterations during tumorigenesis (Lund and van Lohuizen 2004;Baylin 2005;Laird 2005;Ducasse and Brown 2006;Feinberg et al 2006); therefore, abnormal methylation marks may be useful as biomarkers for the early detection and diagnosis of different types of cancer (Paluszczak and Baer-Dubowska 2006 Serum is a very attractive medium for the development of cancer detection assays as is obtained through a simple, relatively noninvasive procedure. Several reports have documented the detection of DNA with cancer-associated changes (mutations, methylation, rearrangements) in the serum of patients; however, its precise origin is unclear.…”
mentioning
confidence: 99%